Identification of Grossing Criteria for Intraoperative Evaluation by Frozen Section of Lung Cancer Resection Margins. (November 2018) - Gagné, Andréanne; Racine, Étienne; Orain, Michèle; Meziou, Salma; Simard, Serge; Couture, Christian; Pagé, Sylvain; Trahan, Sylvain; Ugalde, Paula; Lacasse, Yves; Joubert, David; Joubert, Philippe
Abstract : Because of a lack of official guidelines, systematic use of intraoperative frozen section for the evaluation of surgical margins in lung oncology constitutes standard practice in many pathology departments. This costly and time-consuming procedure seems unjustified as reported rates of positive margins remain low. We aimed to evaluate clinicopathologic criteria associated with positive margins and establish evidence-based recommendations regarding the use of frozen sections. This retrospective cohort included 1903 consecutive patients with a lung resection for malignant neoplasm between 2006 and 2015. Clinicopathologic data were retrieved from medical files. Univariate and multivariate analyses were used to identify variables associated with a positive margin. Receiver operating characteristic curves and a probability table of positive margins based on tumor-margin distance were created. Our results were confirmed in a validation cohort of 27 patients with positive margins. The rate of positive margins was 3.8%. A positive margin status changed the surgical management in 48.6% of patients. A short macroscopic tumor-margin distance was associated with a higher risk of positive bronchovascular and parenchymal margins in univariate and multivariate analyses. Selecting a 2.0 cm tumor-margin distance cut-off for performing a frozen section would result in a 55.3% reduction of intraoperative evaluations, with a risk of missing a positive margin of 0.61%. Overall, we showed that systematic use of frozen section for intraoperative evaluation of surgical margins is unnecessary. A better selection of patients with a higher risk of a positive margin can be achieved with tumor-margin distance as a simple gross evaluation parameter. Abstract : Supplemental Digital Content is available in the text.